Charges Detection of Ultrashort Hirschsprung's Disease (Congenital) with Additional Rectography Examinations - Maulidya Ildsa Mar'athus Nasokha; Ninda Anggresti (Nusantara Science and Technology Proceedings, 2022)
Hirschsprung's disease, occurs 75% occur after six weeks from birth, characterized by aganglionosis of the rectum and sigmoid regions. Rectography is usually used to detect the presence of a rectocele or small-size rectal neoplasms with MR examination. In another study, an examination of the colon can be done with an MRI examination by looking at the enlargement of the colon wall. However, it has the disadvantages of a long duration of examination time, inaccuracy in detecting the entire colon anatomy, and peristaltic artifacts caused by distention of the colon wall. The purpose of this study was to determine the role of rectography examination of neonatal patients with Hirschsprung's disease in the colon in loop examination technique. This type of research is a case study with an observational approach to rectography examination on the neonatal colon in-loop examination techniques. Rectography techniques can be used as an additional examination technique to ascertain the presence of Hirschsprung's pathology, especially in transition areas that are difficult to reach if only using the colon-in-loop examination technique.